THE PHILOSOPHICAL STUDY OF IQBAL'S THOUGHT: The Mystical Experience and the Negation of The Self-Negating Quietism - Roswantoro, Alim (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2017)
The article tries to philosophically explore the Iqbalâ€™s notion of mysticism and the mysticâ€™s attitude in facing the world life. The exploration is focused on his concept of mystical experience and the negation of the self-negating quietism. And from this conception, this writing efforts to withdraw the implication to the passive-active attitude of the worldly life. It is the philosophical understanding of the Islamic mysticism in Iqbalâ€™s philosophy as can be traced and found out in his works, particularly in his magnum opus, â€œThe Reconstruction of Religious Thought in Islamâ€. Mysticism, in Iqbalâ€™s understanding, is the human inner world in capturing reality as a whole or non-serial time reality behind his encounter with the Ultimate Ego. For him, there are two experiences, that is, normal one and mystical one. In efforts to understand mysticism, one has to have deep understanding of the basic characters of human mystical experience that is very unique in nature compared to human normal one.